Women’s Economy Empowerment through the Z-Mart Program of MSMs by BAZNAS South Sumatera Islamic Economic Perspective - Azizah, Warda Aditya; Junaidi, Heri; Azwari, Peny Cahaya (Coopetition : Jurnal Ilmiah Manajemen, 2026)
This study evaluates BAZNAS South Sumatera’s Z-Mart initiative for women owned MSMEs. Through qualitative techniques such as document analysis, in depth interviews with two officials and fourteen female beneficiaries, and field observation. The study identifies both successes and short comings, the initiative effectively doubled or tripled incomes, fortified social networks, and converted mustahik into muzakki, but it still take a top-down charitable approach rather than promoting true empowerment. Unsustainable post program support, slow technology adoption, low beneficiary involvement in decision making, and limited control over business operations are some of the major obstacles. The study suggests developing collective economic institutions, establishing participatory forums, customized assistance package, and putting in place long lasting mentoring systems. Its distinctive feature is in applying the integrated perspectives of Islamic economics and women’s empowerment to analyze the seemingly successful program’s unsustainable model, providing a sophisticated framework for Islamic based economic development that achieves a balance between material and spiritual well being.